(untitled) (Singapore, 2003)
Contents: Proceedings of the Seventeenth Lake Louise Winter Institute, Fundamental Interactions, held from February 17-23, 2002 at the Chateau Lake Louis, Alberta, Canada. Material is devoted to the most recent developments in QCD and electroweak physics.
Keywords: Mô hình chuẩn (Vật lý hạt nhân),Standard model (Nuclear physics); Đo lường,Measurement